KAJIAN LAMA PEMBEKUAN DAN JENIS DAGING TERHADAP KUALITAS DAGING SAPI (Bos primigenius taurus), AYAM BROILER (Gallus domesticus), IKAN PATIN (Pangasius sp) DAN DAGING KAMBING (Capra aegagrus hircus) YANG DITHAWING - Yudi Garnida (Department of Food Technology, Universitas Pasundan, Bandung, 2020)
This research aims to study and analyse the freesing long study and the type of meat to quality beef (Bos primigenius taurus), broiler chicken (Gallus domesticus), fish catfish (Pangius sp) and goat meet (Capra aegagrus hircus) in the thawing. Preliminary research and primary research. Preliminary research on the method of election is the champion and thawing on broiler chicken meat with the analysis of the levels of the protein. The main research was done using 4x2 factorial experiment design pattern in a random design group (RAK) consisting of 2 factors, namely a long freeze 14 days and 20 day, as well as the factors type of beef, chicken broile, meat fish and catfish goat meat with deutonomy as much as 3 times. The result of preliminary research which include analysis of protein levels on broiler chicken meat using some method of thawing obtained resutl of selectd method using microwave thawing at temperature of 30oC with decreased levels of protein most low of 1.21 %. The result of the research show that the main factor of the old chemical response to the freezing of water of water content, levels, and the levels of protein, microbiology test response TPC, as well as the response of organoleptic color, texture and scent on meat that has been frozen, meat type factor effect on the chemical response of water content, and the levels of protein, microbiology test response TPC, as well as the response of organoleptic color, texture and scent meat that has been frozen, but has no effect against a chemical response levels of grey and the interaction between the long freezing meat types and effect on the response organoleptic attribute color and scent of the attribute.